Why do South Asians have high risk for CAD? - Nair, M; Prabhakaran, D (2012)
South Asians have a higher risk for coronary artery disease (CAD) due to both pathophysiological and life course-related risk factors. We performed a literature search and used qualitative synthesis to present evidence for CAD risk factors among South Asians. A large proportion of the higher risk of South Asians for CAD can be explained by conventional risk factors. However, several conditioning factors such as education, socioeconomic status, and fetal programming, and early life influences may contribute to excess CAD risk in South Asians, suggesting the need for a life course approach. Evidence on unconventional risk factors is provocative but comes from small studies. Large-scale, well-designed epidemiological studies are needed for an in-depth understanding of the CAD risk among South Asians. © 2012 World Heart Federation (Geneva). Publishedby Elsevier Ltd. All rights reserved.